1991
DOI: 10.2172/5877485
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental studies of water pretreatment of coal

Abstract: During the past year, a set of water pretreatment experiments was completed on four different coals (Zap, Wyodak, Illinois No. 6, and Pittsburgh No. 8) under two different ranges of conditions (very short and very long pretreatment times). Additional water pretreatment experiments were done with Illinois No. 6 and Pittsburgh seam bituminous coals at selected intermediate points to cover the range of pretreatment behavior. The objective of this work was twofold: 1) to determine how bituminous coals behave durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 11 publications
(29 reference statements)
1
5
0
Order By: Relevance
“…It was no surprise to see the enhanced evolution of H2O, CO, CO2, and SO2 due to oxygen pretreatment, since oxygen reacts with the tire and leads to an increase in oxygen-containing pyrolysis products. It has been reported that oxygen plays a major role in cross-linking of the network structure of coals (Serio et al, 1990(Serio et al, ,1991. Our results revealed that oxygen pretreatment also promotes the cross-linking between macromolecules in tires, which results in reduced tar evolution and the correspondingly higher char yield.…”
Section: Resultssupporting
confidence: 50%
See 1 more Smart Citation
“…It was no surprise to see the enhanced evolution of H2O, CO, CO2, and SO2 due to oxygen pretreatment, since oxygen reacts with the tire and leads to an increase in oxygen-containing pyrolysis products. It has been reported that oxygen plays a major role in cross-linking of the network structure of coals (Serio et al, 1990(Serio et al, ,1991. Our results revealed that oxygen pretreatment also promotes the cross-linking between macromolecules in tires, which results in reduced tar evolution and the correspondingly higher char yield.…”
Section: Resultssupporting
confidence: 50%
“…In studies on coal liquefaction and pyrolysis (Serio et al, 1990(Serio et al, ,1991, it has been found that oxygen functional groups, such as carboxyl and hydroxyl, appear to play a major role in promoting the cross-linking reactions between coal molecules. These cross-linking reactions are usually encountered at low temperatures (<200 °C) prior to the occurrence of bond cleavage in liquefaction or pyrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…As examples of such pretreatment methods, heating under molecular hydrogen with or without added solvent or catalyst, [16][17][18] heating in CO-H 2 O in the pres-ence of basic catalysts 19 or with steam, [20][21][22] and solvent swelling of coals [23][24][25][26][27] were reported to be effective in enhancing conversion and improving the quality of liquid products in liquefaction reactions. Steam treatment was also found effective in the improvement of extraction 28,29 and pyrolysis yields.…”
Section: Introductionmentioning
confidence: 99%
“…Steam treatment was also found effective in the improvement of extraction 28,29 and pyrolysis yields. 21,[28][29][30][31] In solventswelling pretreatment, coal exposed to an effective swelling solvent has been considered to be more accessible to catalyst, molecular hydrogen, and donor solvent. [23][24][25][26][27] Depending on the conditions and the type of additives, combinations of the cleavage of relatively weak bonds, an increase of the labile hydrogen content in coal, and some extent of defunctionalization and depolymerization reactions may be anticipated in the former case.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation